A Smooth Muscle Cell–Enriched Long Noncoding RNA Regulates Cell Plasticity and Atherosclerosis by Interacting With Serum Response Factor. Issue 9 (September 2021) - Ni, Huaner; Haemmig, Stefan; Deng, Yihuan; Chen, Jingshu; Simion, Viorel; Yang, Dafeng; Sukhova, Galina; Shvartz, Eugenia; Wara, A.K.M. Khyrul; Cheng, Henry S.; Pérez-Cremades, Daniel; Assa, Carmel; et al.
Abstract : Objective: Vascular smooth muscle cell (VSMC) plasticity plays a critical role in the development of atherosclerosis. Long noncoding RNAs (lncRNAs) are emerging as important regulators in the vessel wall and impact cellular function through diverse interactors. However, the role of lncRNAs in regulating VSMCs plasticity and atherosclerosis remains unclear. Approach and Results: We identified a VSMC-enriched lncRNA cardiac mesoderm enhancer-associated noncoding RNA (CARMN) that is dynamically regulated with progression of atherosclerosis. In both mouse and human atherosclerotic plaques, CARMN colocalized with VSMCs and was expressed in the nucleus. Knockdown of CARMN using antisense oligonucleotides in Ldlr −/− mice significantly reduced atherosclerotic lesion formation by 38% and suppressed VSMCs proliferation by 45% without affecting apoptosis. In vitro CARMN gain- and loss-of-function studies verified effects on VSMC proliferation, migration, and differentiation. TGF-β1 (transforming growth factor-beta) induced CARMN expression in a Smad2/3-dependent manner. CARMN regulated VSMC plasticity independent of the miR143/145 cluster, which is located in close proximity to the CARMN locus. Mechanistically, lncRNA pulldown in combination with mass spectrometry analysis showed that the nuclear-localized CARMN interacted with SRF (serum response factor) through a specific 600–1197 nucleotide domain. CARMN enhanced SRF occupancy on the promoter regions of its downstream VSMC targets. Finally, knockdown of SRF abolished the regulatory role of CARMN in VSMC plasticity. Conclusions: The lncRNA CARMN is a critical regulator of VSMC plasticity and atherosclerosis. These findings highlight the role of a lncRNA in SRF-dependent signaling and provide implications for a range of chronic vascular occlusive disease states. Abstract : Supplemental Digital Content is available in the text.